Die plek en funksie van "n projek-bestuursmodel in "n makrogemeente - Berg, A. A. van den (HTS teologiese studies, 2003)
The place and function of a project management model in a macro-congregationThe article aims to provide in the need for a project management model for efficient and effective congregation management, following the shift from a modern to a postmodern culture. This model gives congregation members an overall picture of project management and facilitates an understanding of the project management process and its subprocesses. The article argues that project management upholds the congregation's nature, being, character, purpose and structure. It applies the Project Life Cycle of initiating, planning, executing, control-ling and adjourning. It discusses the tools and techniques applied in each of the phases, as well as potential problems. The project management process is put in the context of a project management system and of the congregation and its relevant functions.